(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-146-156 British lower mythology’s influence on H.P. Lovecraft works is understudied. Based on material from a short story “Pickman’s Model” we may trace a number of distinct isomorphisms between the “ghouls” in the story and the supernatural people of fairies in British folklore, such as stealing and changing babies, therianthropy, connections with netherworld and timelessness, social parasitism and links with the activity of witches. The last point is especially interesting in terms of M. Murray’s outdated anthropological theories, highly favoured by Lovecraft. Beyond that, the problems of horror poetics raised in the story harmoniously intertwine with fairies’ role as tutors and inspirers of art. Thus the choice of folkloric material is vital for the story’s goals and poetics. Keywords: H.P. Lovecraft, M. Murray, horror, fairies, witches, folklore, mimesis